Reorganization of the drainage network based on morphostructural controls in passive margins - Cruz, Beatriz Liara da; Archanjo, Raissa Eduarda da Silva; Silva, Renato Villela Mafra Alves da; Santana, Derielsen Brandão; Rios, Guilherme da Silva; Moreira, Vinícius Borges [UNESP]; Oliveira, Thomaz Alvisi de; Fernandes, Nelson Ferreira; Mincato, Ronaldo Luiz; Rubira, Felipe Gomes (Elsevier, 2025)
The reorganization of drainage network and divide migration are fundamental to assessing the influence of tectonics, lithology, climate, base-level changes, and erosional processes on fluvial landscape evolution. However, most studies focus on tectonically active regions, leaving gaps in the understanding of these processes in intraplate settings. In South America, drainage reorganization along passive margin escarpments that drain inland under humid conditions remains poorly explored. The lack of comparative analyses between Neoproterozoic mobile belts and cratons in tectonically quiescent areas highlights the need for a comprehensive approach. In this context, this study investigates the evolution of drainage network and divide migration in a diverse morphostructural setting, considering tectonic legacies in intraplate zones. Using the Upper and Middle Grande River basin in Brazil as a study area, we applied classic morphometric parameters, identified knickpoints, analyzed longitudinal profiles, calculated normalized steepness index (ksn), and assessed drainage divide stability using the χ index. The results indicate that drainage reorganization and topographic rejuvenation are common in tectonically quiescent regions of the Brazilian Atlantic margin due to morphostructural controls and tectonic reactivations. Drainage networks of sub-basins within mobile belts exhibit greater instability than those in cratonic areas. Substrate resistance plays a key role in differential erosion and influences knickpoint formation and distribution. Although the knickpoints of resistant rocks slow down the propagation of erosional waves, differential lithologic resistance, layer inclination, and thickness result in varying degrees of persistence and long-term transient instabilities. These conditions drive river captures, drainage divide rejuvenation, and adjustments in erosional-depositional patterns.
Keywords: Divide migration; Fluvial erosion; Steady state; Transience